A multi-level examination of leadership practices in quality management: implications for organisational performance in healthcare. (14th February 2008) - Akdere, Mesut
Organisations are continuously challenged to become more strategic, productive and cost-effective. As a result, quality management has become increasingly important to achieve desired organisational performance outcomes. Quality management considers leadership an important component to implement and sustain quality products and services to increase organisational performance outcomes. Using a large sample of healthcare professionals, this paper investigates the relationship between leadership practices and organisational performance outcomes from a quality management framework. The findings suggest that leadership practices in quality management are positively related to employee satisfaction, customer satisfaction and financial performance outcomes. Implications for leadership and quality management practice are also discussed.